1999
DOI: 10.1021/ac991119x
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Amperometric Measurements of Zeptomole Quantities of Dopamine Released from Neurons

Abstract: Amperometry with carbon-fiber microelectrodes provides a unique way to measure very small chemical concentration changes at the surface of biological cells. In this work, an investigation of dopamine release from individual neurons isolated from the mouse retina is described. The mice were genetically modified so that, in cells that expressed the protein responsible for catecholamine synthesis, tyrosine hydroxylase, the marker protein, placental alkaline phosphatase, was also expressed. This modification allow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
98
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 127 publications
(101 citation statements)
references
References 35 publications
3
98
0
Order By: Relevance
“…Before analysis, the current wave was digitally refiltered using a smoothing f unction at 8 kHz. Whereas increased filtering uncovered significantly more events in recordings from dispersed acutely dissociated retinal amacrine cells (Hochstetler et al, 2000), in our preparation we observed few such extra events of sufficient amplitude to reach the 5.0Ï« rms noise threshold with filtering as low as 1 kHz (data not shown).…”
Section: Methodsmentioning
confidence: 53%
“…Before analysis, the current wave was digitally refiltered using a smoothing f unction at 8 kHz. Whereas increased filtering uncovered significantly more events in recordings from dispersed acutely dissociated retinal amacrine cells (Hochstetler et al, 2000), in our preparation we observed few such extra events of sufficient amplitude to reach the 5.0Ï« rms noise threshold with filtering as low as 1 kHz (data not shown).…”
Section: Methodsmentioning
confidence: 53%
“…One recording and stimulation site per slice was tested and each slice served as its own precondition control. Fast scan cyclic voltammetry was used to measure electrically evoked DA overflow (34,35). The potential of the carbon fiber electrode was held at ÏȘ0.4 V versus Ag/AgCl between scans and was linearly ramped from ÏȘ0.4 to Ï©1.0 V and then back to ÏȘ0.4 V at a rate of 300 V/s.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, amperometric measurements of current produced during oxidation of released secretory products from adrenal chromaffin cells (Wightman et al, 1991), mast cells (Alvarez de Toledo et al, 1993), PC12 cells (Chen et al, 1994), and mammalian neurons (Jaffe et al, 1998;Hochstetler et al, 2000) have shown that a single fusion event results in a single spike-like current. In contrast, early patch-clamp investigations of exocytosis on mast cells have suggested that neurotransmitter release proceeds in at least two main stages (Breckenridge and Almers, 1987;Zimmerberg et al, 1987).…”
Section: Introductionmentioning
confidence: 99%